Genome‐wide profiling of circular RNAs, alternative splicing, and R‐loops in stem‐differentiating xylem of Populus trichocarpa. Issue 7 (7th April 2021) - Liu, Xuqing; Gao, Yubang; Liao, Jiakai; Miao, Miao; Chen, Kai; Xi, Feihu; Wei, Wentao; Wang, Huihui; Wang, Yongsheng; Xu, Xi; Reddy, Anireddy S.N.; Gu, Lianfeng
Abstract: Circular RNAs (circRNAs) are a recently discovered type of non‐coding RNA derived from pre‐mRNAs. R‐loops consist of a DNA:RNA hybrid and the associated single‐stranded DNA. In Arabidopsis thaliana, circRNA:DNA R‐loops regulate alternative splicing (AS) of SEPALLATA3 ( SEP3 ). However, the occurrence and functions of circRNAs and R‐loops in Populus trichocarpa are largely unexplored. Here, we performed circRNA‐enriched sequencing in the stem‐differentiating xylem (SDX) of P. trichocarpa and identified 2, 742 distinct circRNAs, including circ‐ CESA4, circ‐ IRX7, and circ‐ GUX1, which are generated from genes involved in cellulose, and hemicellulose biosynthesis, respectively. To investigate the roles of circRNAs in modulating alternative splicing (AS), we detected 7, 836 AS events using PacBio Iso‐Seq and identified 634 circRNAs that overlapped with 699 AS events. Furthermore, using DNA:RNA hybrid immunoprecipitation followed by sequencing (DRIP‐seq), we identified 8, 932 R‐loop peaks that overlapped with 181 circRNAs and 672 AS events. Notably, several SDX‐related circRNAs overlapped with R‐loop peaks, pointing to their possible roles in modulating AS in SDX. Indeed, overexpressing circ‐ IRX7 increased the levels of R‐loop structures and decreased the frequency of intron retention in linear IRX7 transcripts. This study provides a valuable R‐loop atlas resource and uncovers the interplay between circRNAs and AS in SDX of P. trichocarpa . Abstract : Examination of circular RNAs in stem‐differentiating xylem of Populus trichocarpa by integration of multi‐omics data, including RNase R‐treated RNA sequencing, DNA:RNA hybrid immunoprecipitation followed by sequencing (DRIP‐seq), and PacBio long‐read isoform sequencing reveals circular RNAs associated with R‐loop structures in regulating alternative splicing.